The Importance Of Idiomatic Dictionary In Arabic Language Acquisition: Students’ Perception/ أهمية المعجم الاصطلاحي في اكتساب اللغة العربية: الرؤية لدى الطلبة - Azman Che Mat; Nazratul Aini Ramli; Ahmad Zulfadhli Nokman; Nor Shaifura Binti Musilehat; Ahmad Fakrulazizi Bin Abu Bakar (Ijaz Arabi Journal of Arabic Learning, 2023)
This study aims to address the issue of students' use of the idiomatic dictionary in their learning of the Arabic language. The idiomatic meaning has become necessary in understanding the linguistic context, especially at the verbal level and the reading text. The dictionaries circulating in libraries may only explain some vocabulary and structures with idiomatic meanings in speech. This study was conducted on 65 students from a public university in which Arabic became one of the communication languages between students and the classroom. The questionnaire distributed to the sample includes several sections, namely the background of the example, knowledge, and expectation of use. Data analysis of the study used SPSS Version 25 to obtain frequency, mean, and correlation tests to achieve the objectives. The result of the study recommends some remarks in the preparation of the terminological dictionary for students at the university level, including the size of the dictionary, the price, and the appropriate contents.